Environmental sustainability profiles assessment of HPLC stability indicating method for quantitation of piracetam and vincamine in pharmaceutical medications - Samya Sh. Alenezi; Ayman A. Gouda; Ragaa El Sheikh; Niaf A. Badahdah; Muneer E Alzuhiri; Ali H. Magrabi; Asim L. Jilani; Ahmed S. Darwish (Talanta Open)
Recently, significant focus has been placed on the development of suitable stability-indicating studies in pharmaceutical analysis. A comprehensive eco-friendly stability-indicating RP-HPLC method has been developed and validated for the determination of piracetam and vincamine in hard gelatin capsule dosage forms. Both components were subjected to various stresses, following the International Conference on Harmonization (ICH) guidelines. Piracetam, vincamine, and their breakdown products were successfully separated using the isocratic elution technique, and both medicinal compounds' quantification was carried out on the Kromasil C18 column at room temperature. The mobile phase consists of 0.05 M potassium dihydrogen phosphate buffer pH 3.5:ethanol absolute (60:40, by volume), at a flow rate of 1.0 ml/min. Detection was implemented at 220 nm, considering the concentration levels of 80–550 and 4.0–28 μg/ml for piracetam and vincamine, respectively. The total analysis time was <5 min, establishing this mentioned chromatographic method as proper for regular quality control evaluations of both medications. The inclusion of ethanol absolute was required in order to obtain a sufficient resolution. Three methods were used to assess the environmental impact: Complementary modified green Analytical Procedure Index (ComplexMoGAPI), the eco-scale calculator, and the Analytical GREEnness metric (AGREE). The chromatographic method's eco-friendly is demonstrated by its final Eco-scale score of 76.5, AGREE score of 0.66, ComplexMoGAPI E-factor was 42 with five green segments, BAGI score of 82.5, and finally whiteness score of 97.5. Obviously, the simultaneous method is accurate, precise, ecofriendly, specific, robust, and rugged. Finally, it can be used successfully for regular quality control analysis of piracetam and vincamine in both their pure form and hard gelatin capsule dosage forms.